2012
DOI: 10.1182/blood-2011-10-322446
|View full text |Cite
|
Sign up to set email alerts
|

EGFL7: a unique angiogenic signaling factor in vascular development and disease

Abstract: EGFL7 is a secreted angiogenic factor that is highly conserved in vertebrates. Most secreted angiogenic signaling molecules, including VEGF and fibroblast growth factor-2, are mainly expressed by nonendothelial cell types such as fibroblasts. In contrast, EGFL7 is unique because it is almost exclusively expressed by and acts on endothelial cells. Egfl7 expression is highest when the endothelium is in an active, proliferating state. This factor acts as a chemoattractant for endothelial cells and binds to compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 63 publications
(197 reference statements)
4
141
0
2
Order By: Relevance
“…Unlike other angiogenic factors (e.g., VEGF), physiological EGFL7 expression and function has been restricted mainly to the endothelial cells where it regulates survival, migration, and differentiation (6). Aberrant expression of EGFL7 has been shown to be involved in tumor growth and disease progression of several solid tumors, including hepatocellular carcinoma, malignant glioma, and breast, lung, and pancreatic cancers (9), but its role in hematopoietic malignancies is currently unknown.…”
Section: Egfl7 | Acute Myeloid Leukemia | Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other angiogenic factors (e.g., VEGF), physiological EGFL7 expression and function has been restricted mainly to the endothelial cells where it regulates survival, migration, and differentiation (6). Aberrant expression of EGFL7 has been shown to be involved in tumor growth and disease progression of several solid tumors, including hepatocellular carcinoma, malignant glioma, and breast, lung, and pancreatic cancers (9), but its role in hematopoietic malignancies is currently unknown.…”
Section: Egfl7 | Acute Myeloid Leukemia | Clinical Outcomementioning
confidence: 99%
“…EGFL7 is a secreted protein of ∼30 kDa and plays an important physiological role in angiogenesis (6)(7)(8). Unlike other angiogenic factors (e.g., VEGF), physiological EGFL7 expression and function has been restricted mainly to the endothelial cells where it regulates survival, migration, and differentiation (6).…”
Section: Egfl7 | Acute Myeloid Leukemia | Clinical Outcomementioning
confidence: 99%
“…The activated Notch signaling downregulates vascular endothelial growth factor receptor (VEGFR)-2 and upregulates VEGFR1, leading to cell differentiation during angiogenesis. 10,14,44 In this study, the expression of Notch1 and Notch4 receptors, Jagged1, Delta-like1, Delta-like4, and HES1 suggests that upregulation of Notch signaling is occurring via a "universal" modulator that does not discriminate between ligand or receptor type.…”
mentioning
confidence: 99%
“…EGFL7, also known as vascular endothelial statin (VEstatin), was initially characterized as a gene specifically expressed by blood vessel endothelial cells in normal organs during development and in adult (Soncin et al, 2003;Parker et al, 2004;Nichol and Stuhlmann, 2012). However, recent studies have reported elevated expression of EGFL7 in several tumors and cancer cell lines, including pancreatic cancer (Zhou et al, 2014), kidney tumors (Xu et al, 2014), malignant gliomas (Huang et al, 2010), hepatocellular carcinomas (Wu et al, 2009;Li et al, 2015), and colon cancers (Diaz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor-like domain multiple 7 (EGFL7) is a secreted protein that contains two EGFlike domains and is conserved across species (Nichol and Stuhlmann, 2012). It was initially regarded as an endothelial cell-specific gene and an important regulator in tubulogenesis during embryonic development (Fitch et al, 2004).…”
mentioning
confidence: 99%